(In) tolerância religiosa: uma proposta de desconstrução de preconceitos - Fischer, Elton (2019)
This dissertation focuses on the phenomenon of intolerant discourses under the bias of discursive complexity, which also reflects the sociocultural complexity of the subjects, seeking alternatives for the deconstruction of these discourses. The research consists of an action research applied to the academics of ULBRA, students of the discipline of Religious Culture, taught by this researcher. We start from the hypothesis that students express certain prejudices regarding religious conceptions different from their own and that these prejudices can be deconstructed in the classroom, privileged place of debate, reflection and critical formation. In this sense, we initially applied a questionnaire to the students to identify possible manifestations of religious prejudice and, from the analysis of the discourses of these students, we searched for strategies of work that could be developed in class in order to contribute to the deconstruction of the preconceptions that we notice exist. This study had, therefore, two main objectives: a) to investigate the conception that the students have on other religious traditions, observing if they manifest prejudices in relation to them; b) to develop a work in the classroom with a view to the deconstruction of biased discourses about the religious practices of various orders. For this, we use discursive semiotics as a theoretical-methodological framework for analysis and also to discourse on discourses of intolerance - mainly based on Barros (2011, 2016) and Landowski (2012, 2014). For studies on religion, we rely on authors such as Brakemeier (2002), Kuchenbecker (2004) and Gaarder (2009) and Botelho (2014). After analyzing the initial questionnaire, which revealed prejudiced discourses about the practices and customs of some religious traditions, we developed a proposal of intervention in the classroom with a view to the deconstruction of these conceptions. At the end of the work developed, some results were evidenced: a) the debates about the theme allowed reflections and exchange of knowledge: b) even after the work carried out there remain some prejudices regarding certain religious practices; c) the information, the socialization of knowledge, the mediation of the debates and the knowledge acquired do not seem to have been as significant as we hoped in the reduction of prejudices, which leads us to think that a work in this direction needs to be carried out continuously and gradually; d) preconceptions and preformed ideas are inherent to the human being, remain in prejudice and be fundamentalist or radical seems to be a choice of each. Finally, to be aware of otherness as an intrinsic element to the social environment and to the construction of identity itself.